Conventional tooth supported overdenture: A case report - Kharel, B; Rai, A; Suwal, P; Parajuli, PK; Limbu, I; Basnet, BB (Journal of Nepalese Prosthodontic Society, 2021)
The present prime concern in dentistry is on preservation of remaining natural teeth. Presence of few teeth in oral cavity help in preserving alveolar ridge integrity, maintain the proprioception, and gives psychological benefit to the patient. Overdenture has proven to be the mainstay of conservative prosthodontic treatment when proper diagnosis, treatment planning, and most importantly, patient compliance are achieved. This paper presents a case report of rehabilitation of a 65 year old patient with multiple missing teeth with tooth supported overdenture in both maxilla and mandible.